Relationship of systemic endothelial function and peripheral arterial stiffness with diabetic retinopathy. Issue 6 (8th December 2014) - Lim, Laurence S; Ling, Lieng H; Cheung, Chui Ming Gemmy; Ong, Peng Guan; Gong, Lingli; Tai, E Shyong; Mathur, Ranjana; Wong, Doric; Foulds, Wallace; Wong, Tien Yin
Abstract : Background: To investigate possible associations between diabetic retinopathy (DR) and systemic vascular endothelial function and arterial stiffness measured using reactive hyperaemia peripheral arterial tonometry. Methods: This was a cross-sectional observational clinical study. Subjects with diabetes were recruited and DR was graded from retinal photographs. Systemic endothelial function was measured using reactive hyperaemia peripheral arterial tonometry (EndoPAT) and expressed as the reactive hyperaemia index (RHI). Peripheral arterial stiffness was measured using the same device and expressed as the augmentation index (AI). Results: In total, 164 eyes of 95 Chinese patients were evaluated. The mean age of the subject eyes was 60.1±8.2 years and 76.8% were men. The mean duration of diabetes was 15.5±9.8 years, and the mean HbA1c was 8.1±1.4%. In age–gender-adjusted models, increasing severity of DR was associated with increasing mean RHI (p=0.001) and increasing mean AI (p<0.001). In multivariate models, adjusting additionally for smoking, mean duration of diabetes, HbA1c and hypertension, the associations with RHI and AI persisted (p=0.011 and 0.001, respectively). In analyses of the dichotomous outcomes clinically significant macular oedema (CSME), moderate DR and vision-threatening DR, AI was a significant predictor of CSME and vision-threatening DR. In multivariate-adjusted models, for every SD increase in AI, the odds of having CSME was 1.78 times higher (95% CI 1.05 to 2.99; p=0.029). For every SD increase in AI, the odds of having vision-threatening DR was 1.73 times higher (95% CI 1.17 to 2.56; p=0.003). Conclusions: Subjects with more severe DR have larger peripheral reactive hyperaemic responses and greater peripheral vascular stiffness. These findings support the link between the microvascular changes of diabetes and macrovascular disease.